Effectiveness of flipped classroom pedagogy: A mixed-methods analysis of adult continuing education—Case study, Egyptian context - Hala Mohamed Said; Islam Al Sawi; Heba Alaa-Eldeen Said (PLoS ONE, 2026)
This mixed-methods study investigated the effectiveness of a flipped classroom model in an adult English as a Foreign Language (EFL) continuing education program in Egypt. A total of 297 learners participated by responding to an online questionnaire, yielding a 72.6% response rate. Learner perceptions were assessed using a Model for Improving Student Learning (MISL) framework across five instructional dimensions, demonstrating strong internal consistency (Cronbach’s α = .72–.93). Quantitative findings indicated positive perceptions across all dimensions (mean scores: 4.30–4.52 on a 5-point scale), with Knowledge Construction rating highest. Multiple regression analysis (R² = .668) identified learner confidence, motivation, engagement, and digital competence as significant predictors of perceived learning. A multivariate analysis (MANOVA) found no significant effect of prior flipped classroom experience. Thematic analysis of open-ended responses revealed increased participation, confidence, and collaboration. The study extends conventional mixed-methods analysis by incorporating sentiment analysis of qualitative responses using Python’s TextBlob library. Sentiment analysis supported these results, with overall positive polarity scores. Findings underscore the role of affective and digital readiness factors in flipped classroom effectiveness, emphasizing the critical importance of well-structured implementation over prior experience with the flipped classroom model, with implications for curriculum design in technology-enhanced adult education, especially in non-Western, resource-constrained settings.